EVALUATING PROJECT-BASED LEARNING AS A PEDAGOGICAL STRATEGY TO PROMOTE ACTIVE LEARNING AND CRITICAL THINKING IN ELEMENTARY SCIENCE LESSONS - Suko Sulasono; Indryani Indryani; Bunga Ayu Wulandari (El Midad, 2025)
This study aims to evaluate the effectiveness of Project-Based Learning (PjBL) in promoting active learning and critical thinking in elementary science lessons. Using a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, the study was conducted in two cycles involving 24 sixth-grade students at SDN 182 Tanjung Jabung Barat. Data were collected through observation sheets assessing visual, oral, listening, writing, and motoric activities, as well as critical thinking tests measured through interpretation, analysis, evaluation, inference, and explanation indicators. The findings show a substantial improvement in students’ learning activeness from 56.2% in Cycle I to 87.4% in Cycle II. Similarly, students’ critical thinking scores increased from 61.5 (moderate) to 83.8 (high). These improvements were achieved through iterative refinement of project activities, which provided structured opportunities for hands-on exploration, collaborative problem-solving, and reflective inquiry. Overall, the study concludes that PjBL effectively fosters a student-centered learning environment that enhances participation and higher-order thinking skills, aligning with the development of twenty-first-century competencies in elementary science education